Ketahanan Masyarakat Penyintas Berbasis Pentagon Aset Pasca Gempabumi Cianjur (Studi di Kecamatan Cugenang, Kabupaten Cianjur, Jawa Barat) - Rahman, Fathin Aulia; Achadi, Abdul Haris (Universitas Gadjah Mada, 2024)
ABSTRACT The Cianjur earthquake was a large shallow earthquake caused by the Cimandiri Fault which was later determined to be the Cugenang Local Fault. The impact of the 5.6 magnitude earthquake devastated most of the Cianjur Regency area, causing a lot of suffering and misery for the post-Cianjur earthquake survivors. Community resilience was needed in facing crises and threats of disaster. This research aimed to: (1) analyzed community resilience; and (2) identified factors that influenced community resilience. This research was quantitative research with a survey method. The research population was based on the sub-district that had the worst impact, namely Cugenang District. The sampling technique used simple random sampling. Data collection techniques used questionnaires and documentation. The data analysis technique used descriptive statistical methods to analyzed levels of resilience, factor analysis methods to identified factors and quantitative description methods to determined community adaptation strategies. The research results showed that the level of resilience of the earthquake survivors in Cugenang District was in the Medium category. The lowest level of resilience according to livelihood assets was natural capital and financial capital. The six most influential factors on resilience were formed, namely socio-economic conditions, the impact of post-disaster assistance & community involvement, post-disaster economic capacity, post-disaster health, and ownership of water sources..